Reported cases of the African Court on Human and Peoples' Rights (2016) / 1 RCACtHPR Part 6 - Attoh, Nonso Robert ([Place of publication not identified] : [Nonso Robert Attoh], 2017)
"A law report containing finalized decisions of the African Court on Human and Peoples' Rights"--Editorial note.
Subject matter index -- Index of international instruments referred to by the Court -- Index of international case law referred to by the Court -- Reported cases.
Publication data from Amazon.com.
Keywords: African Court on Human and Peoples' Rights -- Cases; African Court on Human and Peoples' Rights; Law reports, digests, etc -- Africa; Human rights -- Africa; International human rights courts -- Africa; Human rights; International human rights courts; Law reports, digests, etc; Africa; Court decisions and opinions; Court decisions and opinions; Trials, litigation, etc